2017
DOI: 10.1017/jfm.2017.843
|View full text |Cite
|
Sign up to set email alerts
|

The initial development of a jet caused by fluid, body and free surface interaction. Part 5. Parasitic capillary waves on an initially horizontal surface

Abstract: In Part 3 of this series of papers (Needham et al., Q. J. Mech. Appl. Maths, vol. 61, 2008, pp. 581–614), we studied the free surface flow generated in a horizontal layer of inviscid fluid when a flat, rigid plate, inclined at an external angle $\unicode[STIX]{x1D6FC}$ to the horizontal, is driven into the fluid with a constant, horizontal acceleration. We found that the most interesting behaviour occurs when $\unicode[STIX]{x1D6FC}>\unicode[STIX]{x03C0}/2$ (the plate leaning into the fluid). When $\unicode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the similar, single fluid dam-break flow studied in Uddin & Needham (2015), the inclusion of weak surface tension regularised the solution at small times. This was also the case in the problem studied in Billingham et al (2017), where a numerical solution showed that the oscillatory small time solution emerges after a short, surface-tensiondominated transient. Whilst we could do the same here, including surface tension is not really in the spirit of a simplified problem that is meant to be related to powder snow avalanches, for which the small scale behaviour close to the free boundary is better characterised as particle-laden, multiphase turbulence.…”
Section: Regularization By a Precursor Layermentioning
confidence: 54%
“…In the similar, single fluid dam-break flow studied in Uddin & Needham (2015), the inclusion of weak surface tension regularised the solution at small times. This was also the case in the problem studied in Billingham et al (2017), where a numerical solution showed that the oscillatory small time solution emerges after a short, surface-tensiondominated transient. Whilst we could do the same here, including surface tension is not really in the spirit of a simplified problem that is meant to be related to powder snow avalanches, for which the small scale behaviour close to the free boundary is better characterised as particle-laden, multiphase turbulence.…”
Section: Regularization By a Precursor Layermentioning
confidence: 54%